Case report: Surgical removal of an intradural and intramedullary brainstem foreign body in a young German Shepherd - Thamar-Torres, Oscar; Shores, Andy (Frontiers in Veterinary Science, 2023)
A young, female German Shepherd was presented for evaluation of a progressive, mildly ambulatory tetraparesis with severe neck pain. All segmental reflexes were intact, and the paresis was more severe on the right thoracic and pelvic limbs. Diagnostic imaging (radiographs and computed tomography (CT)) revealed 2 metallic linear foreign bodies lodged at the right side of the cervicomedullary junction. A modification of the previously described ventral craniectomy approach (1) was performed and after removal of a portion of the basioccipital bone using a nitrogen powered drill, the foreign bodies were removed. Over a period of 3 months, the patient made a full recovery.